Cost-effectiveness assessment of transactions internationalwater basins. an application to the andalusian Mediterranean basins - Olmedilla Pérez, Sofía; Gómez-Ramos, Almudena (Observatorio Medioambiental, 2011)
The purpose of this study is to evaluate through a cost-effectiveness approach water use transactions implemented under Water law framework. These measures complement others proposed by Water Plan of the Mediterranian-andallucian Basin. This water transfers were planned in order to improve the environmental conditions of the water body belonging to low Basin of almanzora river. The analysis was developed including uncertainty related with the availability of resources under various water scarcity scenarios. The results show that water use transactions’, from a cost effectiveness approach, has a more favorable assessment than the measures which are explicitly outlined in the river Basin Plan. Furthermore, the study also incorporates a reflection about the suitability of this approach in front of others that consider not just the economic costs, but also others variables, such as social and environmental cost concerned in implementing such measures.